The devolution of a sonic community ritual - Rivera, Robin Daniel Z. (2014)
This paper will deal with the changing soundscape of a particular community in the University of the Philippines Diliman Campus, focusing on the weekly Monday morning flag raising ceremony. The paper will compare how it was celebrated in the past, using earwitness accounts, to how it has been rendered more recently based on a soundscape recording taken in February of 2013. As ritual, flag-raising has devolved over the years. This can be traced to the increase in the level of keynote sounds in and around the campus, the malfunctioning and lack of coordination in the use of the sound devices deployed in the original ritual, and the changes in the soundscapes that index the campus community.
Keywords: University of the Philippines (Diliman); Soundscapes (Auditory Environment)